CONservative TReatment of Appendicitis in Children: a randomised controlled feasibility Trial (CONTRACT). Issue 8 (13th January 2021) - Hall, Nigel J; Eaton, Simon; Sherratt, Frances C; Reading, Isabel; Walker, Erin; Chorozoglou, Maria; Beasant, Lucy; Wood, Wendy; Stanton, Michael; Corbett, Harriet; Rex, Dean; Hutchings, Natalie; et al.
Abstract : Objective: To establish the feasibility of a multicentre randomised controlled trial to assess the effectiveness and cost-effectiveness of a non-operative treatment pathway compared with appendicectomy in children with uncomplicated acute appendicitis. Design: Feasibility randomised controlled trial with embedded qualitative study to inform recruiter training to optimise recruitment and the design of a future definitive trial. Setting: Three specialist paediatric surgery centres in the UK. Patients: Children (aged 4–15 years) with a clinical diagnosis of uncomplicated acute appendicitis. Interventions: Appendicectomy or a non-operative treatment pathway (comprising broad-spectrum antibiotics and active observation). Main outcome measures: Primary outcome measure was the proportion of eligible patients recruited. Secondary outcomes evaluated adherence to interventions, data collection during follow-up, safety of treatment pathways and clinical course. Results: Fifty per cent of eligible participants (95% CI 40 to 59) approached about the trial agreed to participate and were randomised. Repeated bespoke recruiter training was associated with an increase in recruitment rate over the course of the trial from 38% to 72%. There was high acceptance of randomisation, good patient and surgeon adherence to trial procedures and satisfactory completion of follow-up. Although more participants had perforated appendicitis than had been anticipated, treatment pathways were found to be safe and adverse event profiles acceptable. Conclusion: Recruitment to a randomised controlled trial examining the effectiveness and cost-effectiveness of a non-operative treatment pathway compared with appendicectomy for the treatment of uncomplicated acute appendicitis in children is feasible. Trial registration number: ISRCTN15830435 .